Clinical and molecular spectrum associated with Polymerase-γ related disorders. (March 2022) - Jha, Ruchika; Patel, Harshkumar; Dubey, Rachana; Goswami, Jyotindra N.; Bhagwat, Chandana; Saini, Lokesh; K. Manokaran, Ranjith; John, Biju M.; Kovilapu, Uday B.; Mohimen, Aneesh; Saxena, Apoorv; Sondhi, Vishal
Background: POLG pathogenic variants are the commonest single-gene cause of inherited mitochondrial disease. However, the data on clinicogenetic associations in POLG -related disorders are sparse. This study maps the clinicogenetic spectrum of POLG -related disorders in the pediatric population. Methods: Individuals were recruited across 6 centers in India. Children diagnosed between January 2015 and August 2020 with pathogenic or likely pathogenic POLG variants and age of onset <15 years were eligible. Phenotypically, patients were categorized into Alpers-Huttenlocher syndrome; myocerebrohepatopathy syndrome; myoclonic epilepsy, myopathy, and sensory ataxia; ataxia-neuropathy spectrum; Leigh disease; and autosomal dominant / recessive progressive external ophthalmoplegia. Results: A total of 3729 genetic reports and 4256 hospital records were screened. Twenty-two patients with pathogenic variants were included. Phenotypically, patients were classifiable into Alpers-Huttenlocher syndrome (8/22; 36.4%), progressive external ophthalmoplegia (8/22; 36.4%), Leigh disease (2/22; 9.1%), ataxia-neuropathy spectrum (2/22; 9.1%), and unclassified (2/22; 9.1%). The prominent clinical manifestations included developmental delay (n = 14; 63.7%), neuroregression (n = 14; 63.7%), encephalopathy (n = 11; 50%), epilepsy (n = 11; 50%), ophthalmoplegia (n = 8; 36.4%), and liver dysfunction (n = 8; 36.4%). Forty-four pathogenic variants were identified at 13 loci, and these were clustered at exonuclease (18/44; 40.9%), linker (13/44; 29.5%), polymerase (10/44; 22.7%), and N-terminal domains (3/44; 6.8%). Genotype-phenotype analysis suggested that serious outcomes including neuroregression (odds ratio [OR] 11, 95% CI 2.5, 41), epilepsy (OR 9, 95% CI 2.4, 39), encephalopathy (OR 5.7, 95% CI 1.4, 19), and hepatic dysfunction (OR 4.6, 95% CI 21.3, 15) were associated with at least 1 variant involving linker or polymerase domain. Conclusions: We describe the clinical subgroups and their associations with different POLG domains. These can aid in the development of follow-up and management strategies of presymptomatic individuals.